TINDAK TUTUR DALAM SURAT PERJANJIAN KERJA DI PERUSAHAAN MINYAK BOJONEGORO (SPEECH ACT IN THE CONTRACT OF AGREEMENT OF BOJONEGORO OIL COMPANY) - Arif Izzak (Kadera Bahasa, 2016)
One of the speech events involving speaker/writer and listener/reader is letter of agreement. This contract of agreement is between employer and employee. This speech event in the form of contract of aggreement is a process of communication built between the company and the employee within which any kinds of speech act are involved and applied in order to negotiate messages. Dealing with this speech act, the writer would like to study kinds of speech act in the letter of aggreement. Writer wants to identify and describe the category of the speech act applied in the contract. This is important since the momentumof signing the contract is the crucial moment with which problems usually come up between employer and employee. This pragmatic study makes use of descriptive method with qualitative approach. The method used in the data analysis is distributional accompanied by subdivision base technique and followed by extended technique. The results are that there are four kinds of speech act which are involved in the contract of aggreement namely, representative speech act, (assertif), commissive speech act, directive speech act, and declarative speech act. Besides those four kinds of speech act, there are also found the mix-speech acts namely, assertive-commissive, directive-commissive, assertive-declarative, and commissive-declarative. Kind of speech act which occurs the most frequently in the contract of aggreement is directive speech act.